Investigation And Characterization Of Electrolyte For Fluidic Based Pressure Sensor - Fathi, Nur ‘Atiqah Ahmad (2015)

(untitled)
Methanol was used as an electrolyte for one-side-electrode-type proposed by Norzaidi et al (2015). Methanol was easily evaporated and affects the operation and response time of pressure sensor. The objectives of this research are to investigate, characterize and select the best electrolyte for pressure sensor. The parameters observed are dielectric constant, kinematic viscosity and boiling point. Based on the parameters, three electrolytes were selected. There are methanol, ethanol and propylene carbonate. A sensor design with microchannel length of 22 mm, microchannel width of 0.5 mm, microchannel thickness of 0.5 mm and circular membrane radius of 3.2 mm was fabricated. The characterization for the electrolytes was conducted by applying pressure, lifetime and response time measurement. The pressure of 2.5 kPa to 25 kPa was applied and duration of lifetime analysis was set to 7 hours. The sensing mechanism of pressure sensor is based on capacitive changing by implementing the concept of Electrical Double Layer (EDL). Based on the sensor dimensions, calculated capacitance value was 14.34 pF. Based on the results, the suitable electrolyte was propylene carbonate. The measured operating frequency of propylene carbonate was 0.25 kHz and it was determined based on calculated capacitance value. The propylene carbonate has a lowest non-linearity at 0.794%. Propylene carbonate has the longest lifespan more than 7 hours and faster response time at 0.073 s. All the electrolytes were analyzed and propylene carbonate was chosen as the best electrolyte for fluidic based pressure sensor.